Angiotensin-converting enzyme insertion/deletion polymorphism in patients with acute and chronic pancreatitis - Hucl, Tomas; Kylanpää, Marja-Leena; Künzli, Beat; Witt, Heiko B. G.; Lempinen, Marko; Schneider, Alexander; Kemppainen, Esko; Löhr, J.-Matthias; Haas, Stephan; Friess, Helmut; Ockenga, Johann; Rosendahl, Jonas; et al. (European journal of gastroenterology & hepatology, 2009)
Background - Reduction in angiotensin-converting enzyme (ACE) activity has been shown to attenuate pancreatic stellate cell activation and pancreatic fibrosis and suggested as a potential treatment for chronic pancreatitis. The ACE gene insertion/deletion (I/D) polymorphism in intron 16 accounts for nearly half the variation in serum ACE levels. This study determined the frequency of the I/D polymorphism in patients with acute and chronic pancreatitis. - Methods - In total, 887 patients (346 with alcoholic, 443 with nonalcoholic, and 98 with acute pancreatitis) were enrolled, and were compared with 1294 healthy controls. Genotyping of the I/D polymorphism was performed by PCR or melting curve analyses. - Results - No significant differences were found in the prevalence of the ACE-deletion genotype frequencies when patients with alcoholic (27.5%), nonalcoholic (26.4%), and acute pancreatitis (32.7%) were compared with controls (26.9%). Likewise, allele frequencies of the ACE deletion polymorphism were not significantly different in patients with alcoholic (53.8%), nonalcoholic (50.6%), and acute pancreatitis (54.1%) and controls (52.7%). - Conclusion - The I/D polymorphism of the ACE gene was not found to be associated with acute and chronic pancreatitis.
Gesehen am 08.03.2022